Children-menus in restaurants of Portuguese, Hungarian and Croatian shopping centres: A qualitative study. (30th September 2020) - Lima, J P M; Viegas, C; Afonso, C; Tóth, A; Illés, C B; Bittsánszky, A; Šatalić, Z; Filipec, S V; Fabijanić, V; Rocha, A
Abstract: Background: Families to eat out frequently use shopping centres and, there is evidence that children's menus are poor nutritional quality. Obesity rates have increased all over the world, and it has been associated to the observed out of home food consumption. This study aimed to characterise children's menus in shopping center restaurants in Portugal, Hungary and Croatia, as a preliminary study to further develop strategies to intervene. Methods: An observational cross-sectional study was carried out in shopping centres in Portugal, Hungary and Croatia. Only the ones providing a children's menu were selected. Data collection tool was developed by the research team, consisting of a three-section form to identify and characterise the restaurant and analyses the quality of children's menu. Results: Researcher visited 295 restaurants, from which only 69 provided a children's menu. From these 12 restaurants offered gifts associated with it. The most frequently featured items on the menu were hamburgers (22%), grilled or fried chicken (19%), nuggets (17%) and pizza (12%). Potato chips were the most frequent side dish option (33%). Only 11 restaurants offered vegetable soup or vegetables. Although water was available, a variety of soft drinks and sugary fruit juices were also options. Sweet dessert is a common part of the menu. Nutritional information is present in only 13% of the menus. Menu prices do not differ much, Portugal having the higher average (x ̅ = €5.35±1.45). Hungary had the lower average (x ̅ = €4.30±1.50) and Croatia the lowest range (min=€3.00, max=€7.40). Conclusions: Children's menu options have poor quality. Shifting foods offered to children in restaurants has the potential to improve diet quality, reduce excess energy intake and promote healthy eating habits. Key messages: European strategies are needed to promote children healthy food environment. Following aim is to develop and test balanced menus for children among food chains.